PENINGKATAN INTERAKSI BELAJAR DALAM PEMBELAJARAN TEMATIK SISWA KELAS 2 SD NEGERI SAMPANGAN MELALUI MODEL PEMBELAJARAN NUMBER HEAD TOGETHER - Siti Anafiah; Cita Salvatina Devi; Rubiyanta Rubiyanta (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2019)
This study aims to describe the increase of learning interaction in thematic learning in grade 2 students of SDN Sampangan through the Numbered Head Together learning model. This type of research is classroom action research. Data collection techniques use observation, tests, and documentation. This research was carried out at SD Sampangan in Bantul Regency. The time of this study was held in July 2018 to September 2018. The research subjects were grade 2 odd semester 2018/2019 academic year. The object of research is the interaction of student learning in thematic learning. Data analysis techniques used both quantitative and qualitative descriptive. The results showed that the learning interaction of students in Thematic Learning through Numbered Head Together learning models in SDN Sampangan Bantul had increased. Increases occur in student learning interactions that are carried out in two cycles with 3 meetings each. This study obtained the results that the interaction of student learning with students using NHT has increased with the average data acquisition of pre-action of 65 increased 70 in cycle I and increased again to 80 in cycle II. While the teacher and student interaction also increased with the average acquisition in pre-action of 68 increased by 70 in Circular 1 and increased again in cycle 2 by 85. Based on the results of the percentage of completeness in the second cycle that is equal to 85%, this study was said to be successful because it has reached the indicator of the success of a predetermined action.